The Effect of Flexibility, Discipline, and Work Environment on Employee Performance at PT Sinergi Gula Nusantara Gempolkrep Sugar Factory, Mojokerto - Noer Aini Mery Cahyanti; Acep Samsudin (Value Added : Majalah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of work flexibility, work discipline, and work environment on employee performance at PT Sinergi Gula Nusantara Gempolkrep Sugar Factory in Mojokerto. This study uses a quantitative approach with an associative method through multiple linear regression analysis. The research sample consisted of 67 employees from the general finance and plantation departments, selected using a saturation sampling method. The results show that work flexibility, work discipline, and work environment simultaneously have a significant effect on employee performance. Partially, these three variables also have a significant effect on employee performance. This study is expected to serve as a basis for companies to improve employee performance through optimal management of work flexibility, work discipline, and work environment.